Paleoneuroanatomy of the aetosaur Neoaetosauroides engaeus (Archosauria: Pseudosuchia) and its paleobiological implications among archosauriforms - Von Baczko, Belen (2018)
The paleoneuroanatomy of pseudosuchian archosaurs is poorly known, based on direct examination of the internal morphology of braincases and a few artificial endocasts. Among aetosaurs, only one endocast has been described almost a century ago by Case (1921) corresponding to Desmatosuchus spurensis from the Chinle Formation (Norian) of Texas, US, based on a resin cast. Here, we describe the first natural endocast of an aetosaur, Neoaetosauroides engaeus from the Los Colorados Formation (Norian) of NW Argentina, and also developed the first digital endocast of this taxon including the encephalon, cranial nerves, inner ear, and middle ear sinuses. The neuroanatomy of Neoaetosauroides engaeus exhibits several differences from that of Desmatosuchus spurensis despite their phylogenetic proximity, which may be a reflection of their different habits. The information provided by the endocasts of Neoaetosauroides engaeus about its olfactory region and the orientation of its head, based on the inclination of the inner ear, could support the proposal for an animalivorous diet, instead of an herbivorous one as in most aetosaurs. The new information here obtained contributes to the knowledge of the neuroanatomical diversity of archosauriforms and more specifically among pseudosuchians and their paleobiological roles in the Triassic continental communities.